2016
DOI: 10.1007/s11467-016-0562-9
|View full text |Cite
|
Sign up to set email alerts
|

Hopf algebras and Dyson–Schwinger equations

Abstract: In these lectures I discuss Hopf algebras and Dyson-Schwinger equations. The lectures start with an introduction to Hopf algebras, followed by a review of the contribution and application of Hopf algebras to particle physics. The final part of these lectures is devoted to the relation between Hopf algebras and DysonSchwinger equations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…For a pedagogical introduction to some of these concepts, see Refs. [17,[32][33][34][35][36]. In the context of Eq.…”
mentioning
confidence: 99%
“…For a pedagogical introduction to some of these concepts, see Refs. [17,[32][33][34][35][36]. In the context of Eq.…”
mentioning
confidence: 99%
“…Each term X n is produced on the basis of the terms with the lower degrees and furthermore, terms X n s play the role of generators for a Hopf sub-algebra associated to the equation DSE [1,18,19,25,26,40,41]. This presentation of the solution X, which belongs to the completion of H [[α]] with respect to the n-adic topology, has been applied as a starting point to build some new mathematical structures which are capable to encode non-perturbative parameters [33,35,36].…”
Section: Corollary 44 There Exists a Complete And Compact Metric Stmentioning
confidence: 99%
“…The completion of the Hopf algebra H with respect to this topology is the extended Hopf algebra H = n≥0 H n which has elements of the form n≥0 Γ n such that Γ n ∈ H n . It is shown that solutions of combinatorial DSEs belong to this completed Hopf algebra [1,19,25,26,40,41]. On the other side, for each n, X n is a finite Feynman diagram which guarantees the finiteness of the terms Y n s. Each Y n could be constructed from Y n−1 by a growing (not generally uniform) attachment graph sequence.…”
Section: Corollary 44 There Exists a Complete And Compact Metric Stmentioning
confidence: 99%
See 1 more Smart Citation
“…1.1 The Connes-Kreimer Hopf algebra of (rooted) trees. For discussions of the notions of bialgebra and Hopf algebra, see the contribution of Weinzierl [28] in the present volume. The Connes-Kreimer Hopf algebra of (rooted) trees (also called the Butcher-Connes-Kreimer Hopf algebra) is the free algebra H CK on the set of isomorphism classes of combinatorial trees, such as , ,…”
Section: Combinatorial Dyson-schwinger Equationsmentioning
confidence: 99%